Legal pluralism and creative destruction - Matos, José Igreja (2014)
Commencing with an ironic parallel with some concepts of economic sciences, the author calls for an active solidarity of all jurists to safeguard a plural Europe, affected by a severe crisis. Firmly based on the thoughts of the honouree Cunha Rodrigues, the crucial importance of a homogeneous and trustworthy European Judiciary is also emphasized, in order to strengthen advances already provided by European Union Law, especially through the creative and innovative case law from the Court of Justice of the European Union.